The Evolution of Sharia Management: From Classical Muslim Thought to the Challenges of the Modern Global Economy - Havis Aravik; Achmad Irwan Hamzani; Nur Khasanah (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2025)
This research examines the evolution of sharia management from classical Muslim thought to its contemporary application within the modern global economy. The study specifically explores the foundational contributions of classical Muslim scholars to management theory and analyzes the challenges faced by sharia management in responding to increasingly complex economic systems. Employing a qualitative research approach, data were collected through an extensive literature review and in-depth interviews with scholars and practitioners in the field of sharia management. The findings reveal that sharia management has undergone significant transformation, evolving from normative and value-based economic practices in the classical period into more structured, adaptive, and innovative management frameworks in the modern era. Classical Muslim thinkers such as Ibn Khaldun, Al-Farabi, and Al-Ghazali provided enduring theoretical foundations emphasizing ethical governance, justice, accountability, and social welfare, which remain highly relevant in contemporary management discourse. Furthermore, the study identifies key modern challenges, including the integration of sharia management principles within conventional economic systems and the adaptation to emerging financial technologies such as fintech and blockchain. These developments necessitate continuous reinterpretation and institutional adjustment to ensure compliance with sharia principles while maintaining global competitiveness. This research contributes to a deeper understanding of the relevance and adaptability of sharia management in the context of the modern global economy and offers a conceptual foundation for future studies in Islamic management and economic governance